Interplay of Atomic Interactions in the Intermetallic Semiconductor Be5Pt. Issue 44 (24th September 2019) - Amon, Alfred; Svanidze, Eteri; Ormeci, Alim; König, Marcus; Kasinathan, Deepa; Takegami, Daisuke; Prots, Yurii; Liao, Yen‐Fa; Tsuei, Ku‐Ding; Tjeng, Liu Hao; Leithe‐Jasper, Andreas; Grin, Yuri
Abstract: Semiconducting substances form one of the most important families of functional materials. However, semiconductors containing only metals are very rare. The chemical mechanisms behind their ground‐state properties are only partially understood. Our investigations have rather unexpectedly revealed the semiconducting behaviour (band gap of 190 meV) for the intermetallic compound Be5 Pt formed at a very low valence‐electron count. Quantum‐chemical analysis shows strong charge transfer from Be to Pt and reveals a three‐dimensional entity of vertex‐condensed empty Be4 tetrahedrons with multi‐atomic cluster bonds interpenetrated by the framework of Pt‐filled vertex‐condensed Be4 tetrahedrons with two‐atomic polar Be−Pt bonds. The combination of strong Coulomb interactions with relativistic effects results in a band gap. Abstract : Progressive metals : Be5 Pt is a rare representative of semiconductors that are formed by metallic elements only. The gap in the band structure appears due to both relativistic effects and a unique chemical‐bonding situation with polar two‐atom and multi‐atom Pt–Be interactions.